PERLINDUNGAN HUKUM JAMINAN SOSIAL TERHADAP TENAGA KERJA PADA JASA TRANSPORTASI ONLINE - Subakdi Subakdi; Andriyanto Adhi Nugroho (Pamulang Law Review, 2018)
Abstract This research emphasizes Today the company engaged in digital is very rapidly developing, one of them is a digital company in the field of transportation. Drivers of online transportation generally carry out professions in the informal sector through partnership with companies. The relationship that arises between the driver and the company that is not based on work relations has implications for the non-enactment of Law No. 13 of 2003 concerning Labor, This research provides a deeper understanding of how social security legal protection is accepted by online drivers. The research method in this study is normative with a case approach. The results of this study show first, the partnership-based Transportasi service company has not provided social security protection for its partner workers. Second, the regulation in partnership-based labor social security is not clearly regulated in the legislation so that the reason is used as the basis of the online transfortation company to not implement social security workers.